2019
DOI: 10.1080/21870764.2019.1636927
|View full text |Cite
|
Sign up to set email alerts
|

Influence of samarium and iron substitution on structural and electrical properties of barium zirconate titanate solid solutions

Abstract: Solid solutions of (x)SmFeO 3 -(1-x)Ba(Zr 0.05 Ti 0.95 )O 3 : x = 0, 0.21, 0.22 and 0.23 were synthesized by the solid-state reaction route. Le-Bail analysis of the X-ray diffraction data and Raman spectra revealed the presence of the tetragonal phase (P4mm space group 99). The remnant polarization (P r ) was~4.08 µC/cm 2 and 1.04 µC/cm 2 for x= 0 and x= 0.21, respectively, while lossy loops were observed for x≥ 0.22. Canting of the antiferromagnetic spins and ferromagnetic exchange mechanism was responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The ionic radius of Er (1.03 Å) is much smaller compared with that of the host Ba 2+ ion (1.61 Å), which causes a strong compressive strain. Reduced lattice parameters in rare earth doped on the Ba site BTO ceramics are also observed experimentally . Therefore, we have to use the relations where the exchange interaction constants in the defect places are greater compared with the bulk ones, i.e., Jnormald>Jnormalb, Jnormald>Jnormalb.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic radius of Er (1.03 Å) is much smaller compared with that of the host Ba 2+ ion (1.61 Å), which causes a strong compressive strain. Reduced lattice parameters in rare earth doped on the Ba site BTO ceramics are also observed experimentally . Therefore, we have to use the relations where the exchange interaction constants in the defect places are greater compared with the bulk ones, i.e., Jnormald>Jnormalb, Jnormald>Jnormalb.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Reduced lattice parameters in rare earth doped on the Ba site BTO ceramics are also observed experimentally. [57][58][59][60] Therefore, we have to use the relations where the exchange interaction constants in the defect places are greater compared with the bulk ones, i.e., J d > J b , J 0 d > J 0 b . This is contrary to the case of Fe-doped BTO NPs where we have a tensile strain.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This suggested that discharging of the space charge took place to lessen the impact of barriers in grain boundaries at high frequencies. 35,38 The Z' value decreased as frequency rised because charge carriers had less time to drift. At low frequencies, space charge polarization at electrodes was also thought to had a role in the Z' value consistency.…”
Section: Electrical Characterizations Of G-bt-g Structurementioning
confidence: 99%